Assessment of heavy metals contamination in surface sediment and black tilapia (Oreochromis mossambicus) as a monitoring organism in Klang River - Naji, Abolfazl (2012)
Concentrations of Cd, Zn, Ni, Cu, Pb, Fe, T-Hg and Me-Hg in the surface sediments and Oreochromis mossambicus were evaluated to determine the concentration, distribution, overall classification and risk associated with trace metals connected with urban and industrial discharge in the Klang River. Some parameters such as pH, total organic carbon (TOC) and particles sizes in sediment were measured to assess of their impact on metals behavior in the studied area. The concentration of metals ( all in μg∕g,except for Fe in % and Me-Hg in ng/g, dry weight) were as follows: 0.57- 2.19 Cd;31.89-272.33 Zn; 5.96-24.47 Ni; 10.57- 52.87 Cu; 24.23-64.11 Pb; 1.56-3.03 Fe; 0.02-0.45 T-Hg and 0.12-12.57 Me-Hg. The highest (p<0.05) concentration of metals was found in those stations along the vicinity of industrial parks (e.g., Shah Alam industrial area) and highly populated centers (e.g., Klang Valley and Kuala Lumpur). Pearson’s correlation indicated that effectiveness of TOC in controlling the distribution and enrichment of metals was a more important factor than that of the grain size (< 63μm). Sequential extraction technique (SET) was used to evaluate the four fractions (exchangeable, acid-reducible, oxidisable-organic and resistant) in surface sediment. Sequential extraction technique (SET) showed that mean anthropogenic portions of metals were in the order of Zn (60.22) > Cu (56.01) > Cd (45.63) > Ni (42.08) > Pb (33.22) > Fe (10.26). The fractionation of metals in most stations were in the order of resistant > acid-reducible > oxidisable-organic > exchangeable fraction. Since highest concentrations of the metals were found in the residual fraction which indicated that the mobility of these metals in the Klang River was quite low. The degree of sediment contaminations were computed with sediment quality guidelines (SQGs) of threshold effect level (TEL) and probable effect level (PEL), enrichment factor (EF), geoaccumulation index (Igeo) pollution load index (PLI). The results suggested that enrichment factor and geoaccumulation values of Cd were greatest among the studied metals. Likewise, highest PLI were found at the station with high anthropogenic activates. The study revealed that on the basis of computed indexes, Klang River is classified as moderately polluted river. The result also determined that none of studied metals concentrations in the sediments were as high as the PEL value, whereas the concentrations of metals in some stations exceeded the TEL value.